Assistive Technology in the Classroom: Enhancing the School Experiences of Students with Disabilities - Dell, Amy G.; Newton, Deborah A.; Petroff, Jerry G. (Pearson, 2012)
Keywords: Educational technology; United States; United States; Students with disabilities; dept.sed; faculty_collection

Teachers' knowledge base for implementing response-to-intervention models in reading - Spear-Swerling, Louise; Cheesman, Elaine (Reading and Writing, 2012)
This study examined the knowledge base of 142 elementary-level educators for implementing response-to-intervention (RTI) models in reading. A questionnaire assessed participants' professional background for teaching reading, as well as their familiarity with specific assessments, research-based instructional models, and interventions potentially useful in RTI approaches. A multiple-choice knowledge survey patterned after a teacher licensure exam, including items situated in classroom contexts, assessed participants' knowledge about different components of reading, assessment, and RTI practices. Overall, participants obtained the highest scores on a knowledge survey subscale involving fluency/vocabulary/comprehension and the lowest on a subscale involving assessment/RTI practices, with a subscale involving phonemic awareness/phonics in the middle. Mean percentages correct on the subscales ranged from about 58-65% correct. However, participants who said they had prior code-focused professional development outperformed other participants on all survey subscales. General elementary certified teachers performed comparably to special education certified teachers on two out of three subscales, with both groups outperforming unlicensed participants; on the assessment/RTI subscale, only the special educators outperformed unlicensed participants. Most participants were familiar with basic features of RTI such as the three tiered model but were unfamiliar with the research-based instructional approaches and interventions named in the study questionnaire, although participants who had experienced code-focused PD were significantly more likely to be familiar with certain interventions. The study suggests that professional development will be important to enable many educators to implement RTI effectively in reading.
Keywords: Literacy; RTI; Reading; Response to intervention; Teacher knowledge; Teacher preparation; dept.sed; peer-reviewed